Crohn’s disease - Lorenzo y Losada, Humberto; Peri, Lorenzo; Kauffman, Pedro; Grunvald, Eugenio R; Muñoz Monteavaro, Cándido (Cirugía del Uruguay, 1976)
A revision is made of Crohn's disease with reference to a case material which includes 14 patients. Clinical and paraciinical elements permit certainty in diagnosis and presumption of atypical clinical symptoms (occlusion, cronic diarrhea, abdominal masses fistulosis). Medico-surgical treatment of complicated and non complicated symptomatic cas.es is discussed.